Pemanfaatan limbah tebu dan agen hayati bagi peningkatan kualitas beras - Padmini, Oktavia; Wuryani, Sri; Brotodjojo, Rukmowati (Jurnal Agrivet, 2014)
The purpose of this study was to examine the effectof boiler ash which is a waste of sugar industry and liquid organic fertilizer (LOF) to improve the quality of rice. Experiments were set up using split plot and arranged in completely randomized design, with three replicates. Main plots were composed of inorganic fertilizers on 2 levels, namely: 100% farmerâ€™s dose and 50% farmerâ€™s dose plus boiler ash 10 tons/ha. Sub plots was spraying frequency of LOF "Bacteria" and LOF "Plus" with concentration of 15 mL /L consists of five levels, namely: 2, 3, 4, 5, 6 times spraying. The results showed the use of boiler ash can improve the quality of rice. Semi-organic farming system with the additionof boiler ash and spraying the mixture of LOF "Bacteria + LOF â€œPlus" and LOF "Bacteria" four and five times increase the yield and quality of healthy rice including calcium content and amylopectin. Tujuan dari penelitian ini adalah mengkaji pengaruhpemberian abu ketel yang merupakan limbah industria gula dan pupuk organik cair terhadap peningkatan kualitas beras. Percobaan menggunakan Split Plot yang disusun dengan Rancangan Acak Lengkap, diulang tiga kali. Petak Utama adalah pupuk anorganik terdiri atas 2 aras yaitu: 100 % dosis petani dan 50% dosis petani ditambah abu ketel 10 ton/ha. Anak Petak adalah frekuensi penyemprotan POC â€œBakteriâ€ dan POC â€œPlusâ€ konsentrasi 15mL/L air terdiri atas lima aras, yaitu: 2, 3, 4, 5, 6 kali penyemprotan. Hasil penelitian menunjukkan penggunaan limbah abu ketel dapat meningkatkan kualitas beras. Sistem budidaya semi organik disertai penambahan abu ketel dan penyemprotan campuran POC "Bakteria+Plus" dan POC "Bakteriaâ€ empat dan lima kali meningkatkan rendemen dan kualitas beras sehat antara lain kandungan amilopektin dan kalsium.